KONTRIBUSI KEHARMONISAN KOMUNIKASI DALAM KELUARGA TERHADAP PERKEMBANGAN MORALITAS REMAJA/PEMUDAvDI GEREJA PANTEKOSTA DI INDONESIA (GPdI) JEMAAT PERJUANGAN MEDAN TAHUN 2018 - Marioga Pardede (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
This study aims at finding out the Contribution of HarmoniousCommunication in the Family to the Development of Youth Morality in the Church of the Pentecostal Church in Indonesia (GPdI) in Perjuangan Medan in 2018.The population of this study is youth community in GPdi –Perjuangan Medan and the total number is 60 peopleconsisting of 23 boys and 37 girls. Sample of study is 30 persons, consisting 12 boys and 18 girls. The findings of this research show that : (1) tendency of harmonious communication in family (X) of the youth of GPdI Perjuangan Medan is categorized “good” (40%); (2) tendency of moral development (Y) is also categorized “good” (40%); (3) Significant contribution of harmonious communication in family to the development of morality is rcount: rtable is 0.467 > 0.288. It shows that the hypothesis proposed is received, the harmonious communication in family contributes significantly to the development of youth morality. Therefore, it can be concluded that there is a significant contribution of harmonious communication in family to the development of youth morality of GPdI Perjuangan Medan in 2018.